Mexico : Report on the Observance of Standards and Codes; FATF Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report ;, 2009)
This report examines Mexico's observance of Standards and Codes on the Financial Action Task Force on Money Laundering's recommendations for antimoney laundering and combating the financing of terrorism. The Mexican government has instituted unprecedented measures to support law enforcement activities against organized crime and drug trafficking. The authorities have approved an Integral Strategy against Organized Crime, and various key national stakeholders have executed an interagency agreement entitled the National Agreement for Security, Justice, and Legality.